GRIT-an extended REFINE for more executable specifications - Bailes, P.; Chapman, M.; Gong, M.; Peake, I. (Proceedings of 8th Knowledge-Based Software Engineering Conference, 1993)
Knowledge-based software engineering (KBSE) languages should be as expressive as possible and should allow the reflection in executable programs of their non-executable specification origins. REFINE is the KBSE language for the Software Refinery metaprogramming environment. REFINE's expressiveness is extended with recursively-enumerable sets and parallel logical connectives. A subtype system was developed for the otherwise typeless functional language G, hence the name GRIT (G-REFINE InTegration) for this effort. The relationships between REFINE programs and original specifications is made possible by using the recursively-enumerable sets as the basis for a comprehensive system of run-time-checked assertions, which are subject to both set- and type-theoretic compositions.< >